2022
DOI: 10.1155/2022/1630192
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nonpuerperal Uterine Inversion Caused by Cervical Cancer

Abstract: Uterine inversion is a rare puerperal event in the third stage of labor. Nonpuerperal uterine inversion is even rarer and is mainly caused by uterine fibroids, uterine sarcoma, or endometrial cancer. This is the first report of uterine inversion caused by cervical cancer. A 67-year-old woman presented with a 10 cm pelvic mass. Contrast-enhanced magnetic resonance imaging revealed uterine inversion, which was preoperatively diagnosed to be caused by endometrial cancer and was treated using an extended abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recent research has shown that SCNECC is more likely to have mutations in RB1, a proto-oncogenic tumor suppressor, than other neuroendocrine neoplasms of the cervix. 20 Additionally, SCNECC can lead to or coexist with rare complications, such as nonpuerperal uterine inversion, a condition in which the fundus of the uterus prolapses through the cervix, 21 and other pelvic organ prolapses. 22 In recent years, there have been several innovative investigational endeavors T A B L E 1 A summary of the current treatment options for SCNECCs.…”
Section: Further Conceptsmentioning
confidence: 99%
“…Recent research has shown that SCNECC is more likely to have mutations in RB1, a proto-oncogenic tumor suppressor, than other neuroendocrine neoplasms of the cervix. 20 Additionally, SCNECC can lead to or coexist with rare complications, such as nonpuerperal uterine inversion, a condition in which the fundus of the uterus prolapses through the cervix, 21 and other pelvic organ prolapses. 22 In recent years, there have been several innovative investigational endeavors T A B L E 1 A summary of the current treatment options for SCNECCs.…”
Section: Further Conceptsmentioning
confidence: 99%